A Single‐Step Hot Embossing Process for Integration of Microlens Arrays in Biodegradable Substrates for Improved Light Extraction of Light‐Emitting Devices. Issue 2 (23rd January 2020) - Jürgensen, Nils; Fritz, Benjamin; Mertens, Adrian; Tisserant, Jean‐Nicolas; Kolle, Mathias; Gomard, Guillaume; Hernandez‐Sosa, Gerardo
Abstract: Integration of light management solutions relying on biodegradable materials in organic light‐emitting devices could assist the development of sustainable light sources or conformable and wearable display technology. Using industrially relevant processing techniques, it is shown that microlens arrays can be seamlessly integrated into flexible and biodegradable cellulose diacetate substrates to facilitate extraction of the trapped substrate modes in light‐emitting electrochemical cells. The substrates are patterned for light extraction and optimized for scalable printing processes in a single step by thermally embossing microlenses with polydimethylsiloxane molds on one substrate surface and simultaneous flattening of the other. Furthermore, by implementing the biopolymer substrate with microlens arrays, the total volume fraction of biodegradable materials in the microlense equipped device is 99.94%. The embossed microstructures on the biopolymer substrates are investigated by means of scanning electron microscopy and the angular light extraction profile of the devices is measured and compared to ray tracing simulations. Light‐emitting electrochemical cells with integrated microlens array substrates achieve an efficiency enhancement factor of 1.45, exceeding conventional organic light‐emitting diodes on glass substrates with laminated microlens arrays (enhancement factor of 1.23). Abstract : Biodegradable substrates with integrated light management in terms of microlens arrays are fabricated and combined with a flattening process rendering them ready to use for inkjet thin film application in a one‐step hot embossing process with cellulose diacetate. Substrate mode extraction of flexible light‐emitting electrochemical cells shows enhanced efficiency increases in comparison to conventional lamination processes on organic light‐emitting diodes with glass substrates.